Avaliação de alodínia e hiperalgesia cefálica e extracefálica associadas às disfunções temporomandibulares dolorosas - Campi, Leticia Bueno [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
To test whether painful temporomandibular disorder (TMD) is associated with cephalic and extracephalic hyperalgesia and allodynia independent of the other painful conditions (OPC). Methods: Participants were classified according to the presence of painful TMD [Research Diagnostic Criteria for Temporomandibular Disorders (RDC) - Axis I], migraine (The International Classification of Headaches Disorders-II), depression and non-specific physical symptoms (NSPS)(RDC-Axis II). The allodynia and hyperalgesia in the cephalic and extracephalic area were detected after vibrotactile stimulation and algometry respectively. Fisher, Chi-Square and Mann-Whitney Tests were performed with a significant level of 5%. Results: The sample consisted of 250 individuals, 57 men (22.8%), 193 women (77.2%); aged between 19 and 65 years (mean = 35.8 years, SD = 12.8 years), free of fibromyalgia, other types of headaches (not migraine) or OPC. Presence of TMD pain was higher in females (p <0.001) and in the presence of migraine (p <0.001). Painful TMD was associated with higher pain sensitivity in the cephalic (p<0,001) and extracephalic region (p<0,001) independent of the presence of migraine, depression and NSPS; and lower pressure pain threshold (PPT) values in the trigeminal (p<0,001) and extratrigeminal area (p<0,001). Subjects with painful TMD had significantly lower PPT in the cephalic (p<0.001) and extracephalic region (p<0.001), suggesting the presence of secondary hyperalgesia. Conclusion: The highest incidence of hyperalgesia and allodynia among subjects with painful TMD pointed for central sensitization, an important aspect of the chronification processes. Changes involving the central nervous system should be considered in the evaluation and treatment of patients with painful TMD.

Verificar se a disfunção temporomandibular dolorosa (DTM) está associada à hiperalgesia e alodínia cutânea cefálica e extracefálica independente de outras condições dolorosas. Métodos: Os participantes foram classificados pela presença de DTM dolorosa [Critérios de diagnóstico de pesquisa para Disfunções Temporomandibulares (RDC) - Eixo I], migrânea (Critérios da Classificação Internacional de Cefaleia-II), depressão e sintomas físicos não específicos (SFNE) (RDC-Eixo II). A alodínia e hiperalgesia na área cefálica e extracefálica foram detectadas após estimulação vibrotátil e algometria, respectivamente. Testes de Fisher, qui-quadrado e Mann-Whitney foram aplicados com nível de significância de 5%. Resultados: A amostra foi composta por 250 indivíduos, sendo 57 homens (22,8%) e 193 mulheres (77,2%); com idade entre 19 e 65 anos (média = 35,8 anos; DP = 12,8 anos), livres de fibromialgia, outras cefaleias que não preenchiam critérios para migrânea ou outra condição dolorosa crônica. A presença de DTM dolorosa foi maior entre mulheres (p<0,001), e na presença de migrânea (p<0,001). DTM dolorosa foi associada com maior sensibilidade à dor na região cefálica (p<0,001) e extracefálica (p<0,001), independentemente da presença de migrânea, depressão e SFNE. Indivíduos com DTM dolorosa apresentaram limiar de dor à pressão significantemente inferior na região cefálica (p<0,001) e extracefálica (p<0,001), sugerindo a presença de hiperalgesia secundária. Conclusão: A maior incidência de hiperalgesia e alodínia entre os indivíduos com DTM dolorosa sugere envolvimento de sensibilização central, importante aspecto nos processos de cronificação. Os processos envolvendo o sistema nervoso central devem ser considerados durante a avaliação e tratamento dos pacientes com DTM dolorosa.
Keywords: Transtornos da articulação temporomandibular; Hiperalgesia; Articulação temporomandibular; Temporomandibular joint disorders